Efektivitas Kebijakan Literasi Bahasa di Sekolah: Tinjauan Sistematis - Mayzita Dwi amandha; Sugiarto; Muh Takdir; Kamaludin Takdir (Media Manajemen Pendidikan, 2026)
Low levels of language literacy achievement indicate a persistent gap between educational policy formulation and its implementation in school contexts. This study aims to evaluate the implementation of language literacy policies in schools through a Systematic Literature Review (SLR) using the PRISMA protocol, combined with bibliometric analysis. A total of 400 articles published between 2020 and 2025 were identified for bibliometric mapping, and after screening and eligibility assessment based on PRISMA criteria, 19 articles were selected for in-depth analysis. The findings reveal that the evaluation of language literacy policies is still predominantly based on the CIPP model and the use of the Minimum Competency Assessment (AKM), which tend to emphasize administrative compliance. Policy effectiveness is influenced by teachers’ professional capacity, school leadership, and the alignment of policy design with students’ social and linguistic contexts. Cross-study synthesis resulted in a Multi-Level Collaborative Evaluation Model that positions evaluation as an integral part of an evidence-based policy cycle. This study recommends strengthening adaptive and collaborative evaluation systems for language literacy policies. The study is limited by the number of articles reviewed and the dominance of the Indonesian context.